Soluble Receptor for Advanced Glycation End Products (sRAGE) Variation in Human Papilloma Virus (HPV) Infection - The Role of the AGEs-sRAGE Axis in Evaluating the Oxidative Stress - Mircea Tampa; Ilinca Nicolae; Cristina Iulia Mitran; Madalina Irina Mitran; Clara Matei; Corina Daniela Ene; Simona Roxana Georgescu; Mircea Ioan Popa (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
Human papillomavirus (HPV) infects keratinocytes of the skin and mucous membranes, causing a variety of afflictions. Cutaneous and genital warts are the most common HPV-related lesions. Recent studies have highlighted the involvement of oxidative stress as a cofactor in HPV pathogenesis. The relationship between the accumulation of advanced glycation end products (AGEs) and the development of mucocutaneous HPV-related lesions has not been confirmed yet. We have investigated the role of the AGEs-sRAGE axis in patients with HPV-related cutaneous lesions. We have included in the study 41 patients with warts (26 patients with palmoplantar warts and 15 patients with genital warts) and a control group including 28 healthy subjects. We have determined the serum levels of AGEs and circulating soluble receptor for AGEs (sRAGE) by ELISA method. sRAGE levels were lower in patients with palmoplantar warts (p<0.05) and in patients with genital warts (p>0.05) as compared to the control group. We have found higher levels of AGEs in patients with HPV-related cutaneous lesions versus controls, although with no statistical significance. We have obtained a negative correlation between sRAGE and AGEs in patients with palmoplantar warts (r= -0.43, p <0.02) and genital warts (r=-0.47, p>0.05). Our results suggest that the AGEs-sRAGE axis might be involved in the pathogenesis of HPV infection and its modulation could have beneficial therapeutic effects.